The Structure of Oath According to Jurists - Awatli Alrifai, Anas Mh.; Alhababsah, Hamzah H. (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: The study aims to develop a comprehensive understanding of the structure of oaths within the four jurisprudential schools, including common elements among them. It endeavors to clarify the viewpoints of these schools regarding the particulars and restrictions of oaths. Methods: The research adopts an inductive methodology, analyzing the judgments and regulations presented by jurists. It involves a comparative approach between the perspectives of the different schools. Results: The study concluded that jurisprudential schools differed in the construction of oath; The Hanafis make the first consideration of custom, while the Maliki and Hanbali scholars presented the intention; as for the Shafi’is, they adopted the linguistic meaning. - The jurisprudence schools varied in showing integrated controls in building the intention. - The study showed that custom is one of the provisions of the oath to all sects. Conclusion: The wording of the oath needs controls to interpret it, which we can call the premises of the oath. They are agreed among among the scholars but are subjected to differences in its order of priorities. The first group is inclined to precede intentions, followed by situational indicatives; the second precedes current customary practices, and the third prioritized language lexicon. The Maliki school defined situational indicatives from causal point of view, while the Hanbali school based them on provocative causes, and the Hanafi school Close to "oaths Instantly". These oath constraints are important in order to know whether the oath taker has broken his oath and whether consequently he is subjected to expiations.